A new name for the deep-sea chiton Leptochiton clarki Sigwart & Sirenko non Berry (Lepidopleurida: Leptochitonidae) - Sigwart, Julia D.; Sirenko, Boris I. (Zootaxa, 2015)
Recently we described several new species of chitons living in deep water deposits of sunken wood in the southwest Pacific (Sigwart & Sirenko 2012). Among these, one species, Leptochiton clarki Sigwart & Sirenko, 2012, is homonymous with a fossil taxon of the same genus: Leptochiton clarki Berry, 1922. Herein, we replace this homonym with a new name according to International Code of Zoological Nomenclature (ICZN 1999: Art. 57.2).